2022
DOI: 10.1039/d1bm01768c
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid fibrils in superstructures – local ordering revealed by polarization analysis of two-photon excited autofluorescence

Abstract: Protein misfolding products – amyloids – tend to form distinct fibrillar structures of characteristic fold for a given neurodegenerative disease or pathology. Moreover, amyloids (also in intermediate or distorted state)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Protein misfolding and aggregation, that is, amyloid fibrillation, has been proved to be a large factor in such diseases. [1][2][3] Therefore, a new detection method must be established for the process of protein amyloid fibrosis to explore the pathogenesis of these degenerative diseases and screen for the inhibitors of protein fibrosis. [4][5][6][7] Egg white lysozyme is most commonly used in the study of protein fibrosis due to its low price, easy fibrosis, and similarity to the human lysozyme structure.…”
Section: Introductionmentioning
confidence: 99%
“…Protein misfolding and aggregation, that is, amyloid fibrillation, has been proved to be a large factor in such diseases. [1][2][3] Therefore, a new detection method must be established for the process of protein amyloid fibrosis to explore the pathogenesis of these degenerative diseases and screen for the inhibitors of protein fibrosis. [4][5][6][7] Egg white lysozyme is most commonly used in the study of protein fibrosis due to its low price, easy fibrosis, and similarity to the human lysozyme structure.…”
Section: Introductionmentioning
confidence: 99%
“…In all living forms peptides and proteins composed of amino acids give rise to multiple functions regulating the chemistry of life. 1 When the amino acids are arranged in a specific sequence, they can result in structures enabling biological catalysis, [2][3][4] fluorescence, [5][6][7] self-assembly, [8][9][10][11] and many other properties. The self-assembly process of peptides or proteins into amyloid fibrils constitutes an intriguing case.…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit high morphological polymorphism governing their toxicity. , Moreover, self-assembly of amyloidogenic peptides and proteins can lead to the formation of superstructures, namely, spherulites, which are heterogeneous at nano- and microscales. , Spherulites are densely packed spherical superstructures with diameters varying from 5 to 150 μm and composed of unstructured cores and radially growing fibrils . They are characterized by the presence of numerous intermediate states of amyloid aggregates, including mature fibrils . Numerous studies indicated that distinct amyloid fibril morphologies may be more pathogenic than others. , Therefore, rapid structural characterization of amyloids is clinically relevant for diagnosis, classification, and, in further perspective, the treatment of amyloid diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 41 They are characterized by the presence of numerous intermediate states of amyloid aggregates, including mature fibrils. 42 Numerous studies indicated that distinct amyloid fibril morphologies may be more pathogenic than others. 38 , 43 Therefore, rapid structural characterization of amyloids is clinically relevant for diagnosis, classification, and, in further perspective, the treatment of amyloid diseases.…”
Section: Introductionmentioning
confidence: 99%